Sistem Informasi Penjualan Alat Dan Barang Elektronik Di Sahabat Merbau Sentosa Berbasis Web - Pangestu, Randa Yugo (Universitas Labuhanbatu, 2021)
Information systems is a very important role in business activities in a company. Helathy Glorious Electronic stores still use conventional way of processing data on sales transactions, for it requires that information systems can support the smooth running of the sale. The purpose of this study is an attempt to make the system stores the information in the Electronic Helathy Glorious is not computerized and still use conventional way. Of this research are expected to conventional the resulting information system will be capable of overcoming of the system is not computerized.